Implementasi Metode Problem-Based Learning (PBL) Dalam Pembelajaran Matematika Di SD Pelangi - Lailatun Nur Kamalia Siregar; Nurul Dinda Aulia; Sayang Pasaribu; Azwar Siregar; Ardila Salisa Adristi; Putri Novia Ramayani Siregar; Salsa Fadilla (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
One of the learning models included in the 2013 curriculum is the problem-based learning model. The PBL learning model is expected to improve the problem solving abilities of as many students as their problem solving abilities are considered to be still low. The aim of the research carried out by researchers was to determine and verify the impact of implementing the problem-based learning (PBL) model on students' abilities in solving problems, especially mathematics. This research uses a qualitative method by interviewing 4 informants from Pelangi Elementary School. The results of this research are that the problem-based learning (PBL) model has a positive impact on students' problem-solving abilities.